Nursing Rural America : Perspectives From the Early 20th Century. - John Kirchgessner PhD, RN (Springer Publishing Company, 2014)
""Each chapter depicts nurses facing and overcoming a multitude of challenges as they addressed the medical needs of rural Americans. Because of their spirit of acceptance and community cooperation, their outcomes were remarkable: fully immunized communities, a decrease in mortality rates, statewide health policy implementation, and growth in community pride. The resilience of these nurses and their communities serves as a source of professional pride for problems solved and health enhanced.""--Mary S. Collins, PhD, RN, FAAN. Glover-Crask Professor of Nursing. Director, DNP Program. Wegmans.